A common fungicide, Pristine®, impairs olfactory associative learning performance in honey bees (Apis mellifera). (1st November 2021) - DesJardins, Nicole S.; Fisher, Adrian; Ozturk, Cahit; Fewell, Jennifer H.; DeGrandi-Hoffman, Gloria; Harrison, Jon F.; Smith, Brian H.
Abstract: Although fungicides were previously considered to be safe for important agricultural pollinators such as honey bees, recent evidence has shown that they can cause a number of behavioral and physiological sublethal effects. Here, we focus on the fungicide Pristine® (active ingredients: 25.2% boscalid, 12.8% pyraclostrobin), which is sprayed during the blooming period on a variety of crops and is known to affect honey bee mitochondria at field-relevant levels. To date, no study has tested the effects of a field-relevant concentration of a fungicide on associative learning ability in honey bees. We tested whether chronic, colony-level exposure at field-relevant and higher concentrations of Pristine® impairs performance on the proboscis extension reflex (PER) paradigm, an associative learning task. Learning performance was reduced at higher field-relevant concentrations of Pristine®. The reductions in learning performance could not be explained by effects on hunger or motivation, as sucrose responsiveness was not affected by Pristine® exposure. To determine whether Pristine®'s negative effects on learning performance were mediated at a specific life stage, we conducted a cross-fostering experiment that exposed bees to the fungicide either only as larvae, only as adults, or during both stages. We found that exposure across the entire life was necessary to significantly reduce learning performance, although non-significant reductions occurred when bees were exposed during just one stage. Our study provides strong evidence that Pristine® has significant sublethal effects on learning performance. As associative learning is a necessary ability for foraging, our results raise concerns that Pristine® could impair foraging abilities and substantially weaken colony health. Graphical abstract: Image 1 Highlights: Pristine® is a fungicide formulation sprayed on almonds during bloom. Bees from colonies fed higher Pristine® doses had reduced learning performance. Learning reduction was greatest when bees were exposed throughout the lifespan. Responsiveness to sucrose was not affected by Pristine® exposure.